Vector - Cook, Robin, 1940- (New York : G.P. Putnam's Sons, 1999)
A trio of terrorists plan to unleash deadly anthrax in New York City. Doctors Stapleton and Montgomery link a series of unusual cases to the plot.
Keywords: Biological weapons -- Fiction; Forensic pathologists -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction; Adventure fiction; Medical novels